Epitomizing mercury concentrations in incenses as a potential marker to respiratory ailments - Abdul Hadi BuOlayan (Kuwait Journal of Science)
Recent years witnessed the use of incense in aromatherapy, religious festivals, warding negative vibes, and indoor air refreshers at home. Their consequences to respiratory ailments over a long period in relation to pollution from trace metals were least studied. The present study aimed to analyze the elemental mercury (Hg) concentrations directly and indirectly in different marketed incenses and validated their effect on respiratory ailments in residents. Sixteen common brands of incense of pollution interests from the local markets were analyzed using a direct mercury analyzer that measured samples from 0.0015ng/g onwards with precise and reproducible results. Parallelly, residents apportioned in six Governorate areas of environmental interest were provided with questionnaires and sought responses to the use of incenses and their health issues. Analysis revealed high Hg concentrations in the perfume-soaked incenses compared to the non-perfume-soaked incenses besides their significant site-wise variations. The questionnaire from 60 respondents who used ‘Bakhour’ often and were exposed to smoke for >8h showed mild to severe respiratory ailments in line with the indoor-outdoor air quality. Despite the beneficial effect of incenses described in the past, Hg concentration was observed high in the incense that caused varying respiratory ailments which were attributed to the native’s selectivity, regional specificity, and recurrent uses of incenses. This study labeled Hg in incense as an additive bio-indicator to indoor pollution. Furthermore, restricting the burning of unmonitored locally available incense is recommended to prevent health issues and subsequent indoor pollution.